TD 2. Digital tools for sustainable water management (The Philippine Journal of Crop Science, 2018)
Globally, agriculture uses -70% of freshwater and of which, 40% is used for rice cultivation. The alternate wetting and drying (AWD) is one of such water management techniques which can save water up to 30%. However, its adoption has been slow because of many challenges like (a) water is managed by farmers' association, (b) the technology cannot be extrapolated to command area, and (c) it is knowledge, labor and time intensive. IRRI and Phillice have developed a decision tool called AutoMonPH that will automatically inform the farmer, water-user association leader, or irrigation water resources technician on the schedule of irrigation based on the threshold level of "Safe AWD". The study looked into using multiple sensor principles (capacitive, ultrasonic, infrared, resistive) and testing the sensors under varying water conditions (constant and variable head, saline and turbid water) to assess accuracy of water level. It was determined that ultrasonic and capacitance principles exhibited a +/- accuracy of 0.2 to 0.4 cm from actual measured water level values. Different modes of data transmission (Wi-Fi, Sub-Ghz, and GSM) were tested and all forms were found to be useful based on location, connectivity, and costs. As the installation of this decision tool is based on the criteria used for AWD, improvement in site selection practices by shifting to remote based criterion using an unmanned aerial system to assess field topography was explored. This entails drone mapping and assessing elevation to identify field variations, which is difficult to conduct at point based method where selection is done at ground level only. Results from this study will establish baseline information and decision logic for the use of the technology in actual farmer's fields. Scaling up of this technology is expected to improve access to information, foster effective coordination among stakeholders, and promote transparency in water governance thereby catalyzing the adoption of water saving technologies.